Heparin‐Immobilized Polymeric Monolithic Column with Submicron Skeletons and Well‐Defined Macropores for Highly Efficient Purification of Enterovirus 71. Issue 12 (21st September 2018) - Gu, Huimin; Liu, Yibin; Yin, Dezhong; Cai, LuKui; Zhang, Baoliang; Zhang, Qiuyu
Abstract: In this study, glycidyl methacrylate‐based polymerized high internal phase emulsion monolithic column (polyHIPE) with submicron skeletons and well‐defined macropores is prepared and functionalized by immobilizing heparin to obtain a novel affinity chromatographic separation medium for effective purification of Enterovirus 71 (EV71). The pore structure of the obtained monoliths differs significantly from conventional polyHIPE monoliths. The prepared polyHIPE presents well‐defined 3D network skeletons of 0.2–0.5 µm, interconnected macropores of 0.5–2 µm, large specific surface area (47–61 m 2  g −1 ), and excellent permeability ( k  = 1.0 × 10 −13  m 2 ). Further, successful immobilization of heparin is proved by FTIR and XPS and the monoliths display superiority in the purification of EV71 from culture supernatant. The final recovery and binding capacity of EV71 are calculated to be 60% and 152.8 ng per column, respectively. SDS‐PAGE gel electrophoresis and TEM analysis indicate a high efficiency in the removal of impurities from culture supernatant of EV71. This, together with easy fabrication, makes polyHIPE monolith a promising alternative to commercially available monolithic supports for virus purification. Abstract : Glycidyl methacrylate‐based polymerized high internal phase emulsion monolithic column with submicron skeletons and well‐defined macropores is prepared and functionalized by immobilizing heparin to obtain a novel affinity chromatographic separation medium for effective purification of Enterovirus 71, which presents a promising alternative to commercially available chromatographic separation medium for virus purification and is beneficial to the development of vaccine industry.